Optimal systolic array algorithms for tensor product - Mishra, P.K. (Applied mathematics and computation, 2005)
In this paper we examine the computational complexity of optimal systolic array algorithms for tensor product. We provide a time minimal schedule that meets the computed processor lower and upper bounds including one for tensor product. Our principle contribution is to find lower and upper bounds in the algorithm and its implementation for generating function and find processor-time-minimal schedule.